Comparative effectiveness of videotape and handout mode of instructions for teaching exercises: skill retention in normal children - Gupta Garima; Sehgal Stuti (BMC, 2012)
Abstract Background Teaching of motor skills is fundamental to physical therapy practice. In order to optimize the benefits of these teaching and training efforts, various forms of patient education material are developed and handed out to patients. One very important fact has been overlooked. While comparative effectiveness of various modes of instruction has been studied in adults, attention has not been paid to the fact that learning capabilities of children are different from that of adults. The intent of the present study is to compare the effectiveness of video and handout mode of instructions specifically on children. Methods A total of 115 normal elementary-age children aged 10 to 12 years of age were studied. The children were randomized into two groups: A) the video group, and B) the handout group. The video group viewed the video for physical therapy exercises while the handout group was provided with paper handouts especially designed according to the readability of their age group. Results Statistical analysis using the student's't' test showed that subjects of both the video and handout groups exhibited equal overall performance accuracy. There was no significant difference between the groups both in acquisition and retention accuracy tests. Conclusion The findings of the present study suggest that if the readability and instructional principles applicable to different target age groups are strictly adhered to, then both video as well as handout modes of instructions result in similar feedback and memory recall in ten to twelve year-old children. Principles of readability related to the patient age are of utmost importance when designing the patient education material. These findings suggest that the less expensive handouts can be an effective instructional aid for teaching exercises to children with various neuromuscular, rheumatic, and orthopedics conditions and the most costly videotape techniques are not necessarily better.